Liberia : 2022 Article IV Consultation and Fourth Review of the Extended Credit Facility Arrangement, Requests for Waiver of Nonobservance of Performance Criterion, and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for Liberia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Liberia is a fragile, low-income country. Per-capita income remains about a third of the level prior to the civil wars during 1989-2003. After a bout of economic instability, prudent monetary and fiscal policies reduced inflation to just over 5 percent in 2021 and budgets are financed without recourse to central bank credit. Economic growth suffered first from macroeconomic instability and then from the COVID-19 pandemic. Growth rebounded to 5 percent in 2021 and, after a soft patch this year due to Russia's war in Ukraine, should reach 5-6 percent in the medium term if Liberia taps its clear potential through persistent structural reforms and prudent policies. The government's resolve will be tested in the runup to the general elections in September 2023.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Liberia